Efficacy and safety of carbetocin applied as an intravenous bolus compared to as a short-infusion for caesarean section: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Dell-Kuster, Salome; Hoesli, Irene; Lapaire, Olav; Seeberger, Esther; Steiner, Luzius; Bucher, Heiner; Girard, Thierry
Abstract Background The two most commonly used uterotonic drugs in caesarean section are oxytocin and carbetocin, a synthetic oxytocin analogue. Carbetocin has a longer half-life when compared to oxytocin, resulting in a reduced use of additional uterotonics. Oxytocin is known to cause fewer cardiovascular side effects when administered as a short-infusion compared to as an intravenous bolus. Based on these findings, we aim at comparing carbetocin 100 mcg given as a slow intravenous bolus with carbetocin 100 mcg applied as a short-infusion in 100 ml 0.9 % sodium chloride in women undergoing a planned or unplanned caesarean delivery. We hypothesise uterine contraction not to be inferior to a bolus application (primary efficacy endpoint) and greater haemodynamic stability to be achieved after a short-infusion than after a bolus administration, as measured by heart rate and mean arterial blood pressure (primary safety endpoint). Methods/Design This is a prospective, double-blind, randomised controlled, investigator-initiated, non-inferiority trial taking place at the University Hospital Basel, Switzerland. Uterine tone is quantified by manual palpation by the obstetrician using a linear analogue scale from 0 to 100 at 2, 3, 5 and 10 minutes after cord clamping. We will evaluate whether the lower limit of the confidence interval for the difference of the maximal uterine tone within the first 5 minutes after cord clamping between both groups does not include the pre-specified non-inferiority limit of −10. Both haemodynamic secondary endpoints will be analysed using a linear regression model, adjusting for the baseline value and the dosage of vasoactive drug given between cord clamping and 1 minute thereafter, in order to investigate superiority of a short-infusion as compared to a bolus application. We will follow the extension of CONSORT guidelines for reporting the results of non-inferiority trials. Discussion Haemodynamic stability and adequate uterine tone are important outcomes in caesarean sections. The results of this trial may be used to optimise these factors and thereby increase patient safety due to a reduction in cardiovascular side effects. Trial registration Clinicaltrials.govNCT02221531 on 19 August 2014 and www.kofam.chSNCTP000001197 on 15 November 2014.